Immune-related risk score: An immune-cell-pair-based prognostic model for cutaneous melanoma - Li, Mingjia; Long, Xinrui; Bu, Wenbo; Zhang, Guanxiong; Deng, Guangtong; Liu, Yuancheng; Su, Juan; Huang, Kai (Frontiers in Immunology, 2023)
Background: Melanoma is one of the most immunologic malignant tumors with high mortality. There are still a considerable number of patients cannot benefit from the immunotherapy due to the individual difference. This study attempted to build a model of melanoma with immunotherapy by fully considering the individual differences in tumor microenvironment. Methods: Immune related risk score(IRRS) was constructed based on data of cutaneous melanoma from The Cancer Genome Atlas (TCGA) database. The single sample gene set enrichment analysis (ssGSEA) was implemented for calculating the immune enrichment score of 28 immune cell signatures. We performed a pairwise comparison to obtain the score of each cell pair generated by the difference in the abundance of immune cells within each sample. The resulting cell pair score, in the form of the matrix of relative values of immune cells, was the core of IRRS. Results: The AUC of IRRS was over 0.700, and after combined with clinical information, the AUC reached 0.785, 0.817 and 0.801 in 1, 3 and 5 years respectively. The differently expressed genes between the two groups were enriched in staphylococcal infection and estrogen metabolism pathway. The low IRRS group showed better immunotherapeutic response, and exhibited more neoantigens, richer TCR, BCR diversity and higher tumor mutation burden. Conclusion: IRRS has a better effect on the prognosis and immunotherapy effect prediction based on the difference in relative abundance of different types infiltrating immune cells, and could provide support for the further rearch in melanoma.